Predictors of Clinical Efficacy of Cytokine Hemoadsorption in COVID-19 (Clinical Trial) - V. A. Ratnikov; A. N. Sheglov; S. V. Abramovskiy; I. S. Simutis; M. S. Danilov; G. G. Ivanova; A. A. Syrovatskii (Общая реаниматология)
Materials and methods. This study analyzed the results of treatment of 62 patients with severe COVID-19 in the intensive care unit using selective hemoadsorption of cytokines. All patients with severe COVID-19 were admitted to the intensive care unit within 14 days from the disease onset were subdivided into two groups. Group 1 patients (n=32) received on a top of standard treatment the hemoperfusion (HP) procedure for 4 hours, for 2–3 days in a row, using a cytokine sorption column composed of mesoporous styrene-divinilbenzen copolymer matrix. Group 2 patients were not subjected to extracorporeal blood purification. All patients received IL-6 inhibitors at a baseline in accordance to the temporary guidelines. We evaluated factors of unfavorable outcomes by analyzing changes in biochemical markers of systemic inflammatory response and mortality rates in patients of both groups.Results. Initiation of HP later than 10 days from NCI onset (P < 0.001), length of stay in the ICU, extent of lung damage (P = 0.036) and the SOFA (Sequential Organ Failure Assessment) score (P = 0.009) were the most powerful predictors of unfavorable outcome. Levels of systemic inflammatory response markers (interleukin- 6, CRP, D-dimer) in both groups did not significantly affect the survival rates and length of hospital stay (P > 0.05). HP group demonstrated better survival (P < 0.05). Mean hospital stay was 31 and 27 days, ICU stay — 11 and 8 days for Groups 1 and 2, respectively (P < 0.05).Conclusion. Treatment of severe COVID-19 patients with HP using novel domestic hemosorbent composed of styrene-divinilbenzen copolymer matrix resulted in decrease in CRP levels on the first day after application and, with early onset, contributed to a significant increase in survival and decreased hospital and ICU stay. Additional studies are warranted to clarify the optimal timing of the initiation of HP in severe COVID-19 patients.